Formulation, Optimization, and Evaluation of Bioadhesive Xanthan Gum Based Buccal Patch for Sustained Delivery of Ropinirole Hydrochloride (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Parkinson’s disease is a neurological disorder in which there is a gradual loss of brain cells that makeand store dopamine. Ropinirole hydrochloride (ROPH) is an anti-Parkinson’s drug which undergoes extensivelyfirst-pass metabolism, with oral bioavailability 45%. Aim: The study aimed to formulation, optimization, andevaluation of ROPH buccal patch using xanthan gum (XG). Materials and Methods: Solvent casting method wasused to prepare mucoadhesive buccal patch ROPH using XG as a mucoadhesive polymer, polyvinylpyrrolidoneK90 as a film former and polycarbophil and hydroxypropyl methylcellulose K4M as a release retardant.Results and Discussion: The dissolution studies showed sustained release of drug about 97.86% for 8 h followingKorsmeyer-Peppas model (r2=0.989, n = 0.199). The optimization of all prepared batches was carried out by 32factorial designs, the optimized batch F3 showed acceptable physicochemical properties and having swellingindex 286.10%, mucoadhesive strength 26.90 g, tensile strength 0.04±0.01 N/mm2, and in vitro drug release97.86%. Ex vivo permeability was carried out using sheep buccal mucosa and it was found to be increased by fivefolds than that of formulation without penetration enhancer. After histopathological evaluation cellular membranewas found to be intact and did not show any signs of necrosis. Conclusion: Thus, an attempt to formulate a stablemucoadhesive buccal patch was made. The in vitro studies have shown that this is a potential drug delivery systemfor ROPH with good stability and release profile.